MERUMUSKAN PEMIKIRAN EKONOM MUSLIM TENTANG RASIONALITAS DALAM PERILAKU KONSUMEN - Lia Istifhama (Jurnal Keislaman, 2019)
rationality is the characteristic of any action, belief, or desire, that makes their choice optimal under a set of constraints.[1] It is a normative concept of reasoning in the sense that rational people should derive conclusions in a consistent way given the information at disposal. It refers to the conformity of one's beliefs with one's reasons to believe, or with one's actions with one's reasons for action. However, the term "rationality" tends to be used differently in different disciplines, including specialized discussions of economics, sociology, psychology, evolutionary biology and political science. A rational decision is one that is not just reasoned, but is also optimal for achieving a goal or solving a problem.